Adherence Patterns to National Comprehensive Cancer Network Guidelines for Referral of Women With Breast Cancer to Genetics Professionals. (August 2016) - Stuckey, Ashley; Febbraro, Terri; Laprise, Jessica; Wilbur, Jennifer S.; Lopes, Vrishali; Robison, Katina
Abstract : Objective: Genetic predisposition is responsible for 5% to 10% of breast cancer. The National Comprehensive Cancer Network (NCCN) established guidelines delineating appropriate candidates for genetic counseling. This study aims to determine referral patterns for genetic counseling in women who met such guidelines. Materials and Methods: Utilizing an institutional tumor registry, patients from an academic oncology program who met a subset of NCCN guidelines for genetic referrals between 2004 and 2010 were identified (breast cancer diagnosis ⩽50 y without a known BRCA mutation). A retrospective chart review was conducted. Statistics were analyzed using SAS version 9.2. Results: A total of 314 patients were identified and 107 (34.1%) were referred for genetic counseling. Median age at diagnosis was younger for those referred versus not referred (43 and 46 y; P <0.0001). Women were more likely referred with a family history suspicious for an inherited cancer syndrome (67.3% vs. 36.2%; P <0.0001). There was no difference in stage at diagnosis, insurance, or race among women referred. Those patients who choose prophylactic contralateral mastectomy were likely to have been referred for genetic counseling (63.6% vs. 36.4%, P <0.0001). Among patients referred, 77.6% consulted with a genetics counselor, 95.2% underwent genetic testing, and 16.5% had a BRCA mutation. Conclusions: Genetic counseling and testing is being underutilized in women who meet NCCN referral guidelines. Age and family history were noted to be predictive of referral for genetic evaluation. Further research is needed to determine additional factors that may impact not only referral rates but subsequent care for women with possible genetic predispositions to cancer.